1992
DOI: 10.1093/eurheartj/13.suppl_d.121
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and first clinical experiences with an antihypertensive dopamine (DA2) agonist

Abstract: The pharmacokinetic properties and first clinical experiences with the antihypertensive dopamine (DA2) agonist, carmoxirole, are summarized. In man carmoxirole was rapidly absorbed. On oral administration the maximum plasma concentration was reached after 2-3 h. The drug was metabolized, mainly to an ester-type glucuronide, and was excreted (unchanged carmoxirole plus glucuronide) largely by the kidneys. The plasma half-life of the parent compound was 5.5 h. For the dose range tested (0.5 to 1.5 mg) the pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Notably, four of these compounds were dopamine receptor antagonists, including atypical antipsychotics (nemonapride, melperone, and benperidol) and a peripherally active D2 receptor antagonist with antihypertensive properties (carmoxirole). 87 Two compounds (PD-0325901 and selumetinib) were found to reverse the brain transcriptomic expression signature of the somatoform factor by targeting the MAP2K1 gene. One of these, PD-0325901, has potent anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, four of these compounds were dopamine receptor antagonists, including atypical antipsychotics (nemonapride, melperone, and benperidol) and a peripherally active D2 receptor antagonist with antihypertensive properties (carmoxirole). 87 Two compounds (PD-0325901 and selumetinib) were found to reverse the brain transcriptomic expression signature of the somatoform factor by targeting the MAP2K1 gene. One of these, PD-0325901, has potent anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the inhibitory presynaptic receptors, expecially a-2 adrenoceptors, but also adenosine, muscarine, opiate, prostaglandin and dopamine-2 (DA-2) receptors, which, upon stimulation, diminish neuronal noradrenaline (NA) release from varicosities and inhibit adrenergic neurotransmission (2). Previous studies have shown that dopamine (DA) agonists, such as bromocriptine, co-dergocrine, ibopamine and carmoxirole, exert their therapeutic effects in hypertension and/or congestive heart failure at least partly through inhibition of sympathetic nerve activity mediated via DA-2 receptors (3,4).…”
mentioning
confidence: 99%